2020
DOI: 10.18666/jnel-2020-10116
|View full text |Cite
|
Sign up to set email alerts
|

Should I Stay or Should I Go?: Investigating Nonprofit Sector Commitment Among Nonprofit Education Alumni

Abstract: Graduates of nonprofit education programs have seemingly opted in to the nonprofit sector by means of their field of education, but prior research on worker sorting depicts a complex rationale for sector selection. This research study uses a sample of 153 alumni of nonprofit education programs to sort among factors influencing sector commitment. Given that these alumni have seemingly indicated a sector commitment by way of their education field, this analysis investigates factors that may disrupt sector commit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…A sizeable number of studies explore individuals' motivations for choosing work in one sector over another; however, these studies often capture motivation at one point in time with less focus on the variables that influence an individual's commitment to that sector long-term. However, sector commitment, the dedication of an individual in continuing a career within a specific sector of employment, has received increased attention among public and nonprofit researchers as a means of understanding and engendering retention (see Walk et al 2019 for a summary of this research). Sector commitment is an extension of Weisbrod's (1988) theory of managerial sorting, which posits individuals will opt for opportunities within the sector whose incentives match their preferences, and conceives that individuals will stay in a sector that aligns with these preferences.…”
Section: Nonprofit Sector Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A sizeable number of studies explore individuals' motivations for choosing work in one sector over another; however, these studies often capture motivation at one point in time with less focus on the variables that influence an individual's commitment to that sector long-term. However, sector commitment, the dedication of an individual in continuing a career within a specific sector of employment, has received increased attention among public and nonprofit researchers as a means of understanding and engendering retention (see Walk et al 2019 for a summary of this research). Sector commitment is an extension of Weisbrod's (1988) theory of managerial sorting, which posits individuals will opt for opportunities within the sector whose incentives match their preferences, and conceives that individuals will stay in a sector that aligns with these preferences.…”
Section: Nonprofit Sector Commitmentmentioning
confidence: 99%
“…Recent studies have found that the nonprofit sector attracts mission-driven employees while easily losing them because of the inability to pay competitively (Kim & Charbonneu, 2020;Ng & Johnson, 2019). More specifically among the millennial generation-the main generation now entering and increasingly dominating the workforce-findings show that compensation influences younger workers' career decisions (Abouassi et al, 2019;Johnson & Ng, 2016;Walk et al, 2019).…”
mentioning
confidence: 99%
“…From this, extrinsic and intrinsic motivations both fuel sector choice and commitment (for a compilation of this research, refer to . Findings from studies of nonprofit workers suggest that many individuals currently working in the sector seek out these positions intentionally (Stewart & Kuenzi, 2018) with a strong desire to remain in these positions regardless of other mitigating factors or opportunities (Walk et al, 2020). However, evidence documents commitment can change over time (citation redacted for peer review), and we are concerned that nonprofit workers may encounter factors, such as prolonged uncertainty, COVID-19 related trauma, even concomitant concerns from the pandemic coupled with widespread social unrest that distract them from their commitment, prompting them to leave the sector for other career prospects.…”
Section: Nonprofit Sector Commitmentmentioning
confidence: 99%
“…From a study of nonprofit graduate alumni, workers who were fully committed to the nonprofit sector also expressed high extrinsic work expectations (Walk et al, 2020), which should be concerning, as individuals tend to leave their nonprofit careers because of the organizations' inability to offer competitive wages (Kim & Charbonneau, 2018;Ng & McGinnis Johnson, 2019). This finding is especially evident for those in leadership positions who are tempted by compensation in the for-profit sector (Johnson & Ng, 2016), and for the Millennial generation-the largest in the current workforce and those whose long-term career trajectories are very likely to be impacted by COVID-19-who may let compensation drive decisions to switch employers or leave the sector entirely (AbouAssi, McGinnis Johnson, & Holt, 2019;Johnson & Ng, 2016;Walk et al, 2020). Furthermore, findings indicate that about a third of those fully committed to the nonprofit sector do not, in fact, work in it (Walk et al, 2020).…”
Section: Nonprofit Sector Commitmentmentioning
confidence: 99%
See 1 more Smart Citation